Sports injury rate and sports performance: role of low-grade chronic inflammation - Posabella, Giovanni (Progress in Nutrition, 2020)
Summary: As known, inflammation is a protective mechanism against pathogens and other triggers driven by biological molecules (neuropeptides, hormones, cytokines, growth factors). Inflammation is hence a physiological process, but it loses its positive connotation when the anti-inflammatory signal molecules are not able to "suppress" naturally the signs and symptoms of inflammation. In athletes, among the neuro-immuno-endocrine factors controlling homeostasis, one represents the watershed between physiology and pathology, i.e. inflammation, and in particular Low-Grade Chronic Inflammation (LGCI). Starting from this perspective, it is interesting to note how physical exercise induces biphasic responses on many endocrines, and above all, immunological mechanisms, among which the main one is inflammation. Sedentary people are more likely to develop a state of LGCI (with consequent increase in the incidence of related diseases) compared to those who perform a moderate physical activity; the latter will show reduced levels of numerous inflammatory markers, including Interleukin 1-beta (IL-1β), Tumor Necrosis Factor-Alpha (TNF-α) and Interleukin 6 (IL-6), and an increase, at the same time, in anti-inflammatory cytokines ​​and other signal molecules such as Interleukin-10 (IL-10) (6-8). This status and the related cytokine movement has been defined as a “physiological controlled state of inflammation”